Strategi Pemasaran Digital untuk Meningkatkan Pendapatan di Institusi Pendidikan di Era Digital - Ardin Sianipar; Widya Angelia; Natalina Damayanthi (Program Studi Manajemen Pendidikan, 2026)
This study aims to identify digital marketing strategies that enhance revenue streams in educational institutions, with a focus on developing countries such as Indonesia and on advanced technologies like AI and VR. A Systematic Literature Review (SLR) following PRISMA guidelines analyzed 25 peer-reviewed articles from 2020 to 2025, sourced from Scopus, Web of Science, and Google Scholar. Keywords included